Religious Tolerance in Indonesian Language Teaching for Foreign Speaker (BIPA) - Siti Isnaniah; Tiya Agustina; Nurul Fadzilatul Husna (2022)
Indonesian Language Teaching for Foreign Speaker (Pembelajaran Bahasa Indonesia bagi Penutur Asing/BIPA) in Thammasat University Thailand has special uniqueness viewed from point of view of religious tolerance values. BIPA classroom consists of students from various religion such as Buddha, Christianity, and Islam. The background of different believes needs tollerance among religion believers. The objective of this study is to discuss religious tolerance in Indonesian Language Teaching for Foreign Speaker (Pembelajaran Bahasa Indonesia bagi Penutur Asing/BIPA) classroom in Thammasat University Thailand. This research is qualitative descriptive Penelitian ini termasuk using ke dalam jenis techniques of collecting data in form of observation, penelitian interview, and deskriptif kualiatif dengan documentation. The validity of the data uses triangulation. The technique of data analysis uses interactive model. The result of the study shows that Indonesian Language Teaching for Foreign Speaker (Pembelajaran Bahasa Indonesia bagi Penutur Asing/BIPA) teaching in Thammasat Univeraity Thailand has internalized religious tolerance values. It could be seen from 1) Planning step, constructed syllabus has integrated religious tolerance, especially in choosing reading material; 2) Action Step, tolerance value has been taught through respecting and appreciating other's believes which differ from their own ones, being tolerant of religious ceremony, worship places, bersikap and other believes, giving chance to moslem students who do required prayers, and introducing to other Indonesian cultures; 3) Evaluation Step, taken from product-and-process-based assessment based on dilakukan melalui students' competence, without seeing their backgrounds of religion, ethnic, race,nd groups. Along the process of BIPA teaching, character building were focused on tolerant manners, such as respecting, not disturbing public orders, respecting joint desicions, and receiving diversity in their environtment, as well as interpreting tolerance manners in the BIPA classroom and also out of the classroom.